Effects of dietary synbiotic on innate immunity, antioxidant activity and disease resistance of Cirrhinus mrigala juveniles. Issue 80 (September 2018) - Kumar, Pankaj; Jain, K.K.; Sardar, P.
Abstract: The dietary supplementation of synbiotic in Cirrhinus mrigala juvenile (with initial body weight ranging from 2.87 ± 0.01 g to 3.26 ± 0.05 g) was evaluated in terms of changes in innate immunity, antioxidant activity and disease resistance against Aeromonas hydrophilla infection. One hundred eighty acclimatized juveniles of mrigal were randomly distributed in the three replicates of each of four experimental groups i.e. control (without Probiotic and Prebiotic), T1 (High Probiotic + Low Prebiotic), T2 (Low Probiotic + High Prebiotic) and T3 (High Probiotic + High Prebiotic), using completely randomized design (CRD). At the end of the feeding trial for 60 days, fish were challenged by Aeromonas hydrophila and survival rate was recorded for the next 15 days. Bacillus subtilis used as a probiotic source and MOS used as a prebiotic source in the experiment. Results showed that innate immunity was comparatively improved in T3 group. Lysozyme activity and respiratory burst activity (NBT) were significantly (P < 0.05) affected in T3 group. Highest activities of antioxidant enzymes (P < 0.05) were reported in T3 group. Cumulative mortality % was found to be lower in the fish fed dietary synbiotic on T3 group after challenging with Aeromonas hydrophilla infection. The results of this study showed that under the experimental conditions, dietary supplementation of synbiotic had a synergestic effect on enhancing innate immunity and disease resistance of Cirrhinus mrigala (P < 0.05). Highlights: Dietary supplementation of synbiotics leads to increase in growth performance, digestive enzyme and improve gut micro flora activity. Application of dietary synbiotic at optimum inclusion level results to influence the immuno-physiological responses and disease resistance. Use of dietary synbiotic can be an efficient tool to achieve sustainable and safe aquaculture production.